Novel flow cytometric analysis of the blood–brain barrier. (30th April 2015) - Williams, Dionna W.; Tesfa, Lydia; Berman, Joan W.
Abstract The blood–brain barrier (BBB) is primarily comprised of brain microvascular endothelial cells (BMVEC) and astrocytes and serves as a physical and chemical barrier that separates the periphery from the brain. We describe a flow cytometric method using our in vitro model of the human BBB to characterize BMVEC surface junctional proteins critical for maintenance of barrier function, cell viability, and leukocyte adhesion. For this methodology, BMVEC are cocultured with astrocytes in a transwell tissue culture insert to establish the barrier, after which time the BBB are treated with specific agents, and the BMVEC collected for flow cytometric analyses. We use a standard and optimized method to recover the BMVEC from the coculture model that maintains junctional protein expression and cell viability. A novel leukocyte adhesion assay enables a quantitative analysis of peripheral blood mononuclear cell (PBMC) interactions with the BMVEC and can be used to assess the adhesion of many cell types to the BBB. Furthermore, this method enables the concomitant analysis of a large number of adhesion molecules and tight junction proteins on both the BMVEC and adherent PBMC under homeostatic and pathologic conditions. Flow cytometry is an extremely powerful tool, and this technique can also be applied to assess variables not performed in this study, including cell cycle progression, and calcium flux. © 2015 International Society for Advancement of Cytometry